2021
DOI: 10.3389/fonc.2021.691500
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Identified lncBCAS1-4_1 Associated With Vitamin D Signaling and EMT in Ovarian Cancer Cells

Abstract: Long noncoding RNAs (lncRNAs) were identified rapidly due to their important role in many biological processes and human diseases including cancer. 1α,25-dihydroxyvitamin D3 [1α,25(OH)2D3] and its analogues are widely applied as preventative and therapeutic anticancer agents. However, the expression profile of lncRNAs regulated by 1α,25(OH)2D3 in ovarian cancer remains to be clarified. In the present study, we found 606 lncRNAs and 102 mRNAs that showed differential expression (DE) based on microarray data. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Beyond VDR, its classical partner, 1,25(OH) 2 D 3 can also bind to membrane-embedded receptors and affect cytoplasmic signaling cascades through its non-transcriptional activities [ 39 ]. Direct or indirect downstream lncRNA targets of the vitamin D/VDR signaling pathways include AS-HSD17β2 in prostate cancer [ 40 ], H19 in colon cancer [ 41 ], lncBCAS1-4_1 [ 42 ] and TOPORS-AS1 [ 43 ] in ovarian cancer, LUCAT1 in oral squamous cell carcinoma (OSCC) [ 44 ], MEG3 in colorectal cancer (CRC) [ 45 ], MALAT1 in coronary artery disease (CAD) [ 46 ], and HOTAIR in multiple sclerosis [ 47 ]. Created with BioRender.com …”
Section: Functional Link Between Fat-soluble Vitamins (A D E and K) A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond VDR, its classical partner, 1,25(OH) 2 D 3 can also bind to membrane-embedded receptors and affect cytoplasmic signaling cascades through its non-transcriptional activities [ 39 ]. Direct or indirect downstream lncRNA targets of the vitamin D/VDR signaling pathways include AS-HSD17β2 in prostate cancer [ 40 ], H19 in colon cancer [ 41 ], lncBCAS1-4_1 [ 42 ] and TOPORS-AS1 [ 43 ] in ovarian cancer, LUCAT1 in oral squamous cell carcinoma (OSCC) [ 44 ], MEG3 in colorectal cancer (CRC) [ 45 ], MALAT1 in coronary artery disease (CAD) [ 46 ], and HOTAIR in multiple sclerosis [ 47 ]. Created with BioRender.com …”
Section: Functional Link Between Fat-soluble Vitamins (A D E and K) A...mentioning
confidence: 99%
“…This transcript has been shown to attenuate HSD17β2 expression [ 40 ]. lncBCAS1-4_1 is an lncRNA functionally associated with vitamin D signaling in ovarian cancer cells, and is involved in the epithelial-mesenchymal transition in ovarian cancer [ 42 ]. Moreover, expression of MALAT1 is affected by vitamin D status in patients with coronary artery disease and healthy subjects [ 46 ].…”
Section: Functional Link Between Fat-soluble Vitamins (A D E and K) A...mentioning
confidence: 99%
“…A work conducted by Xue et al linked lncBCAS1-4_1 upregulation with EMT and vitamin D signaling. According to the researchers, lncBCAS1-4_1 could eradicate the antitumor function of the 1α,25(OH)2D3 due to ZEB1 upregulation [ 80 ]. The effect of LINC00922 on OC cell proliferation, invasion, migration, and EMT was investigated by Wang et al; in brief, they reported that this lncRNA competitively binds with miR-361-3p, resulting in the upregulation of CLDN1 and activation of the Wnt/β-catenin signaling pathway [ 83 ].…”
Section: Regulation Of Emt By Long Non-coding Rnas In Ovarian Cancer:...mentioning
confidence: 99%
“…Xue et al found over 600 lncRNAs with expression enriched in ovarian cancer cells in several pathways, including vitamin D signaling [ 63 ]. They found that the lncRNA lncBCAS1-4_1 linked vitamin D signaling with epithelial/mesenchymal transition (EMT), an important effect in cancer invasion and metastasis.…”
Section: Long Noncoding Rnas In the Vitamin D Signaling In Cancermentioning
confidence: 99%